2011
DOI: 10.1017/jfm.2011.329
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent boundary layers over permeable walls: scaling and near-wall structure

Abstract: This paper presents an experimental study devoted to investigating the effects of permeability on wall turbulence. Velocity measurements were performed by means of laser Doppler anemometry in open channel flows over walls characterized by a wide range of permeability. Previous studies proposed that the von Kármán coefficient associated with mean velocity profiles over permeable walls is significantly lower than the standard values reported for flows over smooth and rough walls. Furthermore, it was observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
220
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(258 citation statements)
references
References 44 publications
(95 reference statements)
36
220
2
Order By: Relevance
“…Both these above-mentioned approaches yield a U τ value that is within 5% of each other. This value is also similar to the U τ obtained by assuming it to be the maximum of the Reynolds shear stresses as in other studies in the literature (Manes et al 2011). …”
Section: Indirect Estimate Of Skin-frictionsupporting
confidence: 90%
“…Both these above-mentioned approaches yield a U τ value that is within 5% of each other. This value is also similar to the U τ obtained by assuming it to be the maximum of the Reynolds shear stresses as in other studies in the literature (Manes et al 2011). …”
Section: Indirect Estimate Of Skin-frictionsupporting
confidence: 90%
“…As suggested in figure 2(b), the mean velocity profile over a large range of Re K possesses characteristics of both the impermeable boundary and the highly permeable boundary, with a logarithmic velocity profile above the interface (e.g. Suga et al 2010;Manes, Poggi & Ridolfi 2011a) and an inflection point at the interface (e.g. Goharzadeh, Khalili & Jørgensen 2005;Breugem et al 2006).…”
Section: Flow Characteristics For Re Kmentioning
confidence: 92%
“…The relative intensity of the vertical velocity fluctuations therefore increases while the intensity of the streamwise fluctuations decreases (Breugem et al 2006;Suga et al 2010;Manes et al 2011a), enhancing mass transfer (as seen in figure 1). The observed decrease in streamwise turbulence intensity near the interface is most likely related to a change in turbulent structures in the near-wall region, as Breugem et al (2006) found that the signatures of the large-scale motions, typical for the impermeable boundary, disappear for Re K 1.…”
Section: Flow Characteristics For Re Kmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, the permeability along the vertical direction is much higher than the permeability along all directions lying on the x − z plane. As shown by Manes et al (2011aManes et al ( ,b, 2012, enhanced permeability favours momentum transport at the interface between a turbulent ow and a permeable canopy, which weakens the velocity gradient at the canopy top and ultimately the intensity of the associated shear layer. When switching from C S to C 95 , the permeability for the vertical component over the patch top increases much more than the permeability associated with lateral ow movements at the anks.…”
Section: Velocity Measurementsmentioning
confidence: 93%